2022
DOI: 10.1055/a-1889-6534
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Language, Behavioral, Academic, and Social Skills of Cochlear Implant Users in Early Primary Education

Abstract: Background: Cochlear implants improve spoken language skills as well as social and academic performance in children with severe and profound sensorineural hearing loss. Purpose: To compare the social skills, academic competence, and problem behaviors in children with cochlear implants (CIs) and their typical-hearing peers and to investigate the relationship between language skills and social skills, academic competence, and problem behaviors in children with CIs. Research Design: Thirty-two children with CIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Thus, early implantation in the critical language development period reduces the consequences of auditory deprivation. The literature shows that children with CIs before 24 months of age are more likely to achieve age-appropriate auditory and language abilities [ 8 , 18 , 22 ]. In our country, cochlear implantation is approved for children from 12 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, early implantation in the critical language development period reduces the consequences of auditory deprivation. The literature shows that children with CIs before 24 months of age are more likely to achieve age-appropriate auditory and language abilities [ 8 , 18 , 22 ]. In our country, cochlear implantation is approved for children from 12 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that implanting children until to 18 months of age provides better speech recognition outcomes than later implantations [ 16 , 17 ]. A large number of studies also indicate a significant decrease in hearing and speech outcomes if children are implanted after the age of 24–36 months [ 18 , 19 ]. Additionally, while multiple studies have described the clear advantages of bilateral implantation over unilateral implantation in terms of SiN perception [ 20 22 ], a few studies have studied how they perform in comparison to NH peers [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%